Feminist objectivity through privileging of partial truths resolving the epistemic injustice of sexual harassment victims - Baluyot, Aristotle Cedric A. (Lagom: Compendium of CAS Undergraduate Research Abstracts, 2021)
Sexual harassment not only accounts for physical and mental ramifications to victims. Part of its aftermath is the perpetuation of epistemic injustice used to empower the harasser and repress their victims by rendering them unreliable. This is attributed to the existence of patriarchy in traditional epistemology and its communities that make discussions on sexual harassment lenient to the dominant demographic. As such, this thesis rejects traditional epistemology and its corresponding methods, and espouses the nature of sexual harassment as a multifaceted problem. In line with Donna Haraway's situated knowledge thesis, which contends that only partial perspectives guarantee objective truth, this thesis also claims to promote feminist objectivity in sexual harassment cases and resolve the epistemic injustice by privileging their claims to truth in social discourses.